2012
DOI: 10.1111/j.1537-2995.2012.03958.x
|View full text |Cite
|
Sign up to set email alerts
|

Processed residual pump blood in cardiac surgery: the Processed Residual Blood in Cardiac surgery trial

Abstract: Ultrafiltration of residual CPB volume in adults undergoing isolated CABG surgery does not reduce the need for transfusion or bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…This study demonstrated no effect of ultrafiltration on the transfusion of homologous blood, postoperative haemorrhage or discharge Hb. 357 In contrast to this study, another prospective RCT in 573 patients receiving ultrafiltration at the end of CPB (treatment) or no ultrafiltration (control) showed a lower prevalence of early morbidity [66 of 284 (23.2%) vs 117 of 289 (40.5%); P ¼ 0.0001] and lower blood transfusion requirements (1.66 ± 2.6 vs 2.25 ± 3.8 U/patient; P ¼ 0.039) in the ultrafiltration group. 297 In a similar, smaller RCT (60 patients), also comparing ultrafiltration to no ultrafiltration at the end of CPB, ultrafiltration was associated with increased inflammatory response, reduced chest tube drainage (598 ± 123 ml vs 848 ± 455 ml; P ¼ 0.04) and fewer blood transfusions (0.6 ± 0.6 U/patient vs 1.6 ± 1.1 U/patient; P ¼ 0.03).…”
Section: Iib Cmentioning
confidence: 99%
“…This study demonstrated no effect of ultrafiltration on the transfusion of homologous blood, postoperative haemorrhage or discharge Hb. 357 In contrast to this study, another prospective RCT in 573 patients receiving ultrafiltration at the end of CPB (treatment) or no ultrafiltration (control) showed a lower prevalence of early morbidity [66 of 284 (23.2%) vs 117 of 289 (40.5%); P ¼ 0.0001] and lower blood transfusion requirements (1.66 ± 2.6 vs 2.25 ± 3.8 U/patient; P ¼ 0.039) in the ultrafiltration group. 297 In a similar, smaller RCT (60 patients), also comparing ultrafiltration to no ultrafiltration at the end of CPB, ultrafiltration was associated with increased inflammatory response, reduced chest tube drainage (598 ± 123 ml vs 848 ± 455 ml; P ¼ 0.04) and fewer blood transfusions (0.6 ± 0.6 U/patient vs 1.6 ± 1.1 U/patient; P ¼ 0.03).…”
Section: Iib Cmentioning
confidence: 99%
“…However, a study in CABG patients by Whitlock et al showed no benefit in reducing blood loss or allogeneic transfusions when post-CPB hemoconcentration of circuit contents was applied. 26 A small study of patients undergoing myocardial revascularization examined how MUF and CUF affected intraoperative coagulation and fibrinolytic systems. 27 Other than an increase in antithrombin III levels in the MUF group compared to CUF and control patients, there were no differences in platelet counts, coagulation parameters or fibrinolytic systems.…”
Section: Commentmentioning
confidence: 99%
“…Several previous studies have compared different processing procedures of RPB (unprocessed, centrifugation, or ultrafiltration), but it is still unclear which one is the best choice. The study by Whitlock et al was the largest ( n = 197) randomized controlled trial and showed no significant difference in postoperative transfusion rate and chest drainage between the ultrafiltration and unprocessed groups. Compared to their study, the RPB was more concentrated with a higher hematocrit in this study (29% in Whitlock’s study vs. 49% in this study), which might yield better results on increase in Hgb.…”
Section: Discussionmentioning
confidence: 99%